Intelligent decision support framework for assessment of alternative vehicle technologies in transportation system: A sustainable approach toward environmental remedy - Ibrahim Alrashdi; Ahmed M. Ali; Karam M. Sallam; Mohamed Abdel-Basset (Sustainable Futures)
The transportation system has the most considerable negative impacts on the environment due to greenhouse gas (GHG) emissions, so various governments seek to reduce GHG emissions by using the best alternative vehicle technologies in the transportation system. This paper presents a framework for selecting the best alternative vehicle technology in Egypt to reduce the emission of GHG toward sustainability. Multi-criteria decision-making (MCDM) is used to deal with various conflicting criteria. This paper uses two MCDM methods: stepwise weight assessment ratio analysis (SWARA) and root assessment method (RAM). This study extends the SWARA and RAM methods under single-valued neutrosophic sets (SVNSs). The SVN-SWARA method is used to compute the criteria weights, and the SVN-RAM method is used to rank the alternatives. This study used seven main criteria, 40 sub-criteria, and 12 alternative vehicle technologies. The results in weights of criteria show that social criterion has the highest importance, and the market criterion has the lowest importance. The results in the rank of alternatives show the Electric vehicles (alternative) are the best choice for GHG emission reduction and for achieving sustainability in the transportation system in Egypt. The sensitivity and comparative analysis showed that the rank of alternatives is stable under different scenarios and that the proposed methodology is effective.